A proteomic approach reveals possible molecular mechanisms and roles for endosymbiotic bacteria in begomovirus transmission by whiteflies. Issue 11 (13th November 2020) - Kliot, Adi; Johnson, Richard S; MacCoss, Michael J; Kontsedalov, Svetlana; Lebedev, Galina; Czosnek, Henryk; Heck, Michelle; Ghanim, Murad
Abstract: Background: Many plant viruses are vector-borne and depend on arthropods for transmission between host plants. Begomoviruses, the largest, most damaging and emerging group of plant viruses, infect hundreds of plant species, and new virus species of the group are discovered each year. Begomoviruses are transmitted by members of the whitefly Bemisia tabaci species complex in a persistent-circulative manner. Tomato yellow leaf curl virus (TYLCV) is one of the most devastating begomoviruses worldwide and causes major losses in tomato crops, as well as in many agriculturally important plant species. Different B. tabaci populations vary in their virus transmission abilities; however, the causes for these variations are attributed among others to genetic differences among vector populations, as well as to differences in the bacterial symbionts housed within B. tabaci . Results: Here, we performed discovery proteomic analyses in 9 whitefly populations from both Middle East Asia Minor I (MEAM1, formerly known as B biotype) and Mediterranean (MED, formerly known as Q biotype) species. We analysed our proteomic results on the basis of the different TYLCV transmission abilities of the various populations included in the study. The results provide the first comprehensive list of candidate insect and bacterial symbiont (mainly Rickettsia) proteins associated with virus transmission. Conclusions: Our data demonstrate that the proteomic signatures of better vector populations differ considerably when compared with less efficient vector populations in the 2 whitefly species tested in this study. While MEAM1 efficient vector populations have a more lenient immune system, the Q efficient vector populations have higher abundance of proteins possibly implicated in virus passage through cells. Both species show a strong link of the facultative symbiont Rickettsia to virus transmission.